Challenges in germination of Neltuma caldenia in semi-arid regions: optimization of germination protocols, influence of saline stress and seed quality - Dalzotto, Daniela; Sharry, Sandra; Piñuel, Lucrecia; Boeri, Patricia (Revista de la Facultad de Ciencias Agrarias UNCuyo, 2025)
Global climate change presents challenges to arid and semi-arid ecosystems, impacting native species such as Neltuma caldenia, endemic to Argentina. This underscores the importance of understanding germination processes for both conservation programs and the restoration of degraded areas. We aimed to evaluate the germination rate of N. caldenia seeds from the south Espinal, using various scarification methods (chemical, mechanical and physical), and temperatures (25-30°C). Additionally, we investigate the effects of accelerated aging (0-96 h at 45°C and 100 relative humidity) and different saline solution concentrations during germination (0-0.6 M NaCl). Our results show that all scarification treatments effectively break seed dormancy while temperature significantly affects germination rates. Prolonged storage (0 to 96h) decreased seed viability. Moderate NaCl levels (0-0.2 M) did not affect germination, but higher concentrations inhibited it completely, with a threshold of -1.81 MPa osmotic potential. Understanding the impact of environmental stressors on seed germination can inform the development of effective conservation strategies among these climate change pressures. Highlights: Shorter duration chemical scarification method (10 minutes) and mechanical scarification were statistically more efficient than the other treatments. Temperature significantly influences germination capacity, with optimal rates achieved at 30–35°C, aligning with the precipitation patterns of the region. caldenia seeds may demonstrate greater resilience to high-temperature and humidity conditions, probably due to higher vigor. Salinity tolerance during germination extends up to -0.90 MPa, highlighting adaptability to saline environments of caldenia compared to other Neltuma species.